(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Understanding is not always obtained through higher education but can also be obtained from short, solutive training. Cilengkrang District is an area in Bandung Regency with tourism potential that can increase regional income, considering its geographical conditions in the highlands with tourism potential in the form of a view of the city of Bandung as well as hills and waterfalls. However, the utilization of this potential is less than optimal which after being identified and observed has problems related to the application of document administration. So that this training was held aiming to provide an understanding in applying basic level administration. The implementation method begins with identification and observation to find out the root of the problem and the solution, then socialization is carried out to provide apperceptions about the problems that occur and the solutions offered and interviews to recruit eligible participants, followed by implementation or materials and competency tests. The conclusions and results obtained in this training are the feasibility of the training participants so that they are considered capable of applying basic level administration in managing tourist attractions which are potential villages in receiving regional income as evidenced by the final value of the training participants. Even though the administration still uses conventional methods, it does not rule out the possibility for participants to apply administration digitally.